Uji Potensi Ekstrak Daun Sirsak (Annona muricata linn) Dengan Minyak Zaitun Terhadap Daya Bunuh Kutu Rambut (Pediculus humanus capitis) - Titania Wahyu Eka Dinata; Abdul Chamid; Muhammad Sungging Pradana (Jurnal SainHealth, 2023)
Head lice (Pediculus humanus capitis) commonly infecting children in most countries. Soursop leaves (Annona muricata Linn) contain acetogenin compounds. The acetogenin compound functions as an anti feedent, some people also use olive oil to kill head lice, because olive oil contains flavonoids. The purpose of this study was to see the potential of soursop leaf extract with olive oil to kill head lice. This type of research is experimental. The method used to obtain soursop leaf extract is the maceration method. The results of giving soursop leaf extract (Annona muricata Linn) with olive oil (Olea eruopaea) on the mortality of head lice (Pediculus humanus capitis) in controls showed no dead head lice, 10% concentration of 4 dead head lice, 20% concentration 6 dead head lice, 30% concentration of 8 dead head lice observed every 15 minutes. Based on these results, it can be seen that the combination of soursop leaf extract and olive oil has the potential to kill head lice.Keywords: Soursop leaf extract, olive oil, head lice